ANALISIS FAKTOR YANG MEMPENGARUHI TINGKAT KOLEKTIBILITAS PEMBIAYAAN PADA KSPPS MUAMALAH BERKAH SEJAHTERA DAN KPRI USAHA KITA DI SURABAYA - Viola Nurahma Putri; Bayu Arie Fianto (Universitas Airlangga, 2019)
This study was conducted to determine the effect of occupation, financing and distance to the level of financing collectability using logistic regression. The data in this study came from KSPPS Muamalah Berkah Sejahtera and KPRI Usaha Kita in Surabaya. By using purposive sampling method, there are 183 members in KSPPS Muamalah Berkah Sejahtera and 88 members in KPRI Usaha Kita that meet the criteria. The results of this study indicate that distance has a significant effect on the level of collectibility of financing in KSPPS Muamalah Berkah Sejahtera. Whereas at the KPRI Usaha Kita level, the financing collectibility is significantly influenced by gender and distance.Keywords: Collectibility, Logistic Regression, Financing, Koperasi